2018
DOI: 10.1523/jneurosci.2407-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Mechanisms of Prioritizing Selection for Rejection in Visual Search

Abstract: In visual search, the more one knows about a target, the faster one can find it. Surprisingly, target identification is also faster with knowledge about distractor-features. The latter is paradoxical, as it implies that to avoid the selection of an item, the item must somehow be selected to some degree. This conundrum has been termed the "ignoring paradox", and, to date, little is known about how the brain resolves it. Here, in data from four experiments using neuromagnetic brain recordings in male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 71 publications
(27 reference statements)
6
24
1
Order By: Relevance
“…This interference occurred throughout the coherent moving stage, suggesting that sustained inhibition of the distractor direction could benefit the speed change detection in the target direction. Indeed, it has been suggested that distractors cannot be ignored before being selected in visual search (Donohue, Bartsch, Heinze, Schoenfeld, & Hopf, 2018). The decoding results in the distractor cueing condition demonstrated that monitoring the distractor direction while attending to the target direction serves as a means to reduce the between-direction interference.…”
Section: Discussionmentioning
confidence: 93%
“…This interference occurred throughout the coherent moving stage, suggesting that sustained inhibition of the distractor direction could benefit the speed change detection in the target direction. Indeed, it has been suggested that distractors cannot be ignored before being selected in visual search (Donohue, Bartsch, Heinze, Schoenfeld, & Hopf, 2018). The decoding results in the distractor cueing condition demonstrated that monitoring the distractor direction while attending to the target direction serves as a means to reduce the between-direction interference.…”
Section: Discussionmentioning
confidence: 93%
“…[101][102][103] It is selectively elicited by distractors, and is independent from other lateralized components reflective of attentional selection, such as the N2pc 76,93,100,104 and N1pc. 104 Accordingly, the Pd has been proposed to reflect a mechanism that prevents or terminates the allocation of attention toward a salient distractor. 10,105 Although in many cases the Pd follows the N2pc 76,102,[106][107][108] or N1pc 104 in the ERP waveform as predicted by the ignoring paradox, growing evidence indicates that salient distractors can also be inhibited (as evidenced by a Pd) in the absence of any neural evidence for attentional selection (e.g., the absence of an N2pc).…”
Section: First Trial Last Trialmentioning
confidence: 99%
“…The Pd, a transient positivity contralateral to the distractor, is especially relevant as its amplitude inversely scales with behavioral measures of distractor interference (102)(103)(104). It is selectively elicited by distractors, and is independent from other lateralized components reflective of attentional selection, such as the N2pc (76, 94,101,105) and N1pc (105). Accordingly, the Pd has been proposed to reflect a mechanism that prevents or terminates the allocation of attention towards a salient distractor (10,106).…”
Section: Post-distractor Inhibition: Pre-attentive and Reactive Inhibmentioning
confidence: 99%
“…Although in many cases the Pd follows the N2pc (76, 103, 107-109) or N1pc (105) in the ERP waveform as predicted by the ignoring paradox, growing evidence indicates that salient distractors can also be inhibited (as evidenced by a Pd) in the absence of any neural evidence for attentional selection (e.g., the absence of an N2pc) (10). Notably, in the majority of these studies, the experimental design allowed for statistical learning, either because the target and distractor identities were fixed (i.e., same color/shape) across trials (95,102,110,111), or because there was a high probability distractor location (86).…”
Section: Post-distractor Inhibition: Pre-attentive and Reactive Inhibmentioning
confidence: 99%